Cancer-associated stroke: Pathophysiology, detection and management (Review) - Dardiotis, Efthimios; Aloizou, Athina-Maria; Markoula, Sofia; Siokas, Vasileios; Tsarouhas, Konstantinos; Tzanakakis, Georgios; Libra, Massimo; Kyritsis, Athanassios; Brotis, Alexandros; Aschner, Michael; Gozes, Illana; Bogdanos, Dimitrios; et al. (International journal of oncology, 2019)
Numerous types of cancer have been shown to be associated with either ischemic or hemorrhagic stroke. In this review, the epidemiology and pathophysiology of stroke in cancer patients is discussed, while providing vital information on the diagnosis and management of patients with cancer and stroke. Cancer may mediate stroke pathophysiology either directly or via coagulation disorders that establish a state of hypercoagulation, as well as via infections. Cancer treatment options, such as chemotherapy, radiotherapy and surgery have all been shown to aggravate the risk of stroke as well. The clinical manifestation varies greatly depending upon the underlying cause; however, in general, cancer‑associated strokes tend to appear as multifocal in neuroimaging. Furthermore, several serum markers have been identified, such as high D‑Dimer levels and fibrin degradation products. Managing cancer patients with stroke is a delicate matter. The cancer should not be considered a contraindication in applying thrombolysis and recombinant tissue plasminogen activator (rTPA) administration, since the risk of hemorrhage in cancer patients has not been reported to be higher than that in the general population. Anticoagulation, on the contrary, should be carefully examined. Clinicians should weigh the benefits and risks of anticoagulation treatment for each patient individually; the new oral anticoagulants appear promising; however, low‑molecular‑weight heparin remains the first choice. On the whole, stroke is a serious and not a rare complication of malignancy. Clinicians should be adequately trained to handle these patients efficiently.